Phenol hydrogenation to cyclohexanol catalysed by palladium supported on CuO/CeO2 - Kasabe, Mirabai M.; Kotkar, Vaibhav R.; Dongare, Mohan K.; Umbarkar, Shubhangi B. (Chemistry-an asian jounrnal, 2023)
Hydrogenation of phenol to cyclohexanone/cyclohexanol is an important reaction in production of nylon-6, nylon-66 and in petroleum industry. Liquid phase phenol hydrogenation over Pd-CuO/CeO2 was carried out under mild conditions. Palladium impregnated over CuO/CeO2 synthesized by co-precipitation method showed excellent catalytic activity for phenol hydrogenation (99% conversion with 80% cyclohexanol yield) at 90 degrees C and 10 bar H-2 pressure in water. Commercial 10%Pd/C showed only 8% phenol conversion under identical conditions. The detailed characterization revealed significant improvement in surface area of ceria after addition of CuO and decrease in crystallite size with creation of defects in CeO2 lattice. XPS analysis showed Pd loading on CuO/CeO2 to cause hydrogen spillover on the surface leading to increase in the oxygen vacancies. The interaction of phenol with catalyst surface studied by detailed FTIR analysis, revealed activation of phenol on oxygen vacancy of ceria as phenoxide ion with perpendicular orientation of aromatic ring on catalyst surface.
Keywords: Cyclohexanol; Hydrogen spillover; oxygen vacancies; Pd-CuO/CeO2; phenol hydrogenation